Stress-Easing Effect of Diacyl Glyceryl Ethers on Anxiety-Related Behavior in Mice - Rong Jiang; Takeshi Ohkubo; Toshihiko Sato; Nobuyuki Sakai (Foods)
Stress and anxiety are significant psychological challenges in modern society, which have led to a rapidly growing market for functional foods, including those reported to relieve stress, as alternatives to psychoactive drugs. Among these, diacyl glyceryl ethers (DAGE) derived from deep-sea shark liver oil have gained attention for their strong antioxidant properties and potential mental health benefits. Building on preliminary evidence suggesting DAGE’s efficacy in enhancing stress resilience and modulating biochemical pathways associated with reduced oxidative stress, the present study aimed to examine their effects on stress responses in two specific mouse strains. Each mouse was fed either a DAGE-infused diet or a control diet for three weeks. Their stress responses were evaluated using three behavioral tests: the elevated plus maze, open-field, and forced swimming tests. The DAGE-fed mice displayed lower stress responses than the control mice in the initial trial of each test. Specifically, DAGE-fed mice demonstrated increased time spent in the open arms in the elevated plus maze and more time spent in the center of the open field, suggesting reduced anxiety. Additionally, in the forced swimming test, DAGE-treated mice displayed reduced immobility times, indicating potential antidepressant effects on the mice. These findings suggest the potential of DAGE to bolster stress resilience in mice, emphasizing their promise for further studies in human stress management.